Kefahaman Takdir Ulama Melayu dalam Merawat Kecelaruan Jiwa: Understanding the Concept of Destiny from the Perspective of Malay Ulama in Treating Mental Disorders - Abd. Latif , Faizuri; Zainal Abidin , Mohd Syukri (Jurnal Usuluddin, 2021)
Mental disorders are one of the elements resulting from stress and emotional strain that befall an individual. The stress could be caused by various factors such as losing a loved one, strapped for cash, family issues, health issues, and more. Furthermore, the spread of the Covid-19 pandemic has negatively and tremendously affected ones emotion and well-being. Various alternatives have been sought out to treat said syndrome, including approaches suggested by the Westerners. However, these approaches cannot resolve many psychological problems as they do not possess religious elements. Hence, there is a need for approaches with religious elements to ensure the effectiveness of the treatment. This study uses a qualitative approach of documentation and text analysis to determine how far the approaches of Malay scholars; through understanding destiny can cope with the issue of mental disorders.